2005
DOI: 10.1111/j.1365-2621.2005.tb11464.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Oxidation in Frankfurters with Increasing Levels of Added Rosemary Essential Oil: Effect on Color and Texture Deterioration

Abstract: ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: : : : : The dev The dev The dev The dev The development of pr elopment of pr elopment of pr elopment of pr elopment of protein o otein o otein o otein o otein oxidation as assessed b xidation as assessed b xidation as assessed b xidation as assessed bxidation as assessed by the total carbonyl content and its influence on y the total carbonyl content and its influence on y the total carbonyl content and its influence on y the total carbonyl content and its influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
111
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(135 citation statements)
references
References 34 publications
17
111
0
7
Order By: Relevance
“…The decrease in L* values using chicken meat after day 5 was reported in previous research studies (Chouliara et al, 2007;Al-Hijazeen et al, 2016a, b). Several research study were reported that RE have a potential antioxidant activity which help to maintain meat color stability and especially a* values (Estévez et al, 2005;Rohlik & Pipek, 2012;Kumar et al, 2015). However, the effect of E-300 was very low and not significant (P > 0.05) at day 7 of storage time.…”
Section: Color Measurementmentioning
confidence: 90%
See 3 more Smart Citations
“…The decrease in L* values using chicken meat after day 5 was reported in previous research studies (Chouliara et al, 2007;Al-Hijazeen et al, 2016a, b). Several research study were reported that RE have a potential antioxidant activity which help to maintain meat color stability and especially a* values (Estévez et al, 2005;Rohlik & Pipek, 2012;Kumar et al, 2015). However, the effect of E-300 was very low and not significant (P > 0.05) at day 7 of storage time.…”
Section: Color Measurementmentioning
confidence: 90%
“…Finally, E-300 and BHA samples treatment was less acceptable by the panelist compared to the other treatments additives. This effect of RE on the sensory attributes of different meat preparation had been reported in various studies (Thongtan et al, 2005;Estévez et al, 2005;Feng et al, 2016). On addition, RE prevents the alteration in protein functionality caused by oxidation which may affect meat color and their texture characteristics (Estévez et al, 2005).…”
Section: Sensory Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that pork meat is darker and redder than CBM. Several authors have demonstrated that certain natural pigments present in additives, such as hydrolyzed potato protein, rosemary essential oil and tapioca starch can influence the final color of meat emulsions (Nieto et al, 2009;Estevez et al, 2005).Emulsion stability The differences in emulsion stability of raw batters formulated with CBM and PLM were not significant (p > 0.05) (Table 1), with Control and T4 having the highest emulsion stability. T3 had the highest total expressible fluid and fat loss, so had the lowest emulsion stability.…”
mentioning
confidence: 89%